Para un canon de marginales, malos y malditos: Jaime Rest en CEAL y Ediciones Librerías Fausto - Crespi, Maximiliano (Centro de Estudios de Teoría y Crítica Literaria, IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. UNLP, 2009)
This paper seeks to account for the link between the last period in Jaime Rest's criticism and his work both on the editorial project of Centro Editor de América Latina and on the design of the 'Novel and Short Story' catalog of Ediciones Librerías Fausto. Rest's critical production between the mid 60s and the late 70s is examined, and a detailed description of his work as editor during the same period is presented. The purpose of such comparison is to establish relationships of contiguity and interference between the two areas of work in the context of a cultural and intellectual field marked by repression and censorship